2023
DOI: 10.1108/aia-09-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of caregiver experience for children with ASD: an in-depth perspective

Neha Gupta,
Manya Khanna,
Rashi Garg
et al.

Abstract: Purpose This study aims to examine the psycho-emotional and social experiences of caregivers of children with autism spectrum disorder. Various facets of the caregiving experience are explored, including the feelings and thoughts of the parents/caregivers, such as the resilience experienced in their journey, how they coped with the challenges and also their positive experiences. Design/methodology/approach In this study, these aspects of the caregiving experience are broadly probed using semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…On the other hand, when spouses struggle to maintain the marital alliance, when they exhibit differing attitudes, and when there is an uneven distribution of responsibilities between them, the lack of a shared sense of partnership can potentially damage the quality of the relationship between parents of ASD children. This supports previous studies on parents of children with ASD that reported the communication between the couple to be a key factor in maintaining a marriage (Gupta et al 2023). Likewise, dyadic coping of parents of children with disabilities, which includes facing the challenges as a team, can have an important role in preserving the marital relationship (Brien-Bérard and des Rivières-Pigeon 2023).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, when spouses struggle to maintain the marital alliance, when they exhibit differing attitudes, and when there is an uneven distribution of responsibilities between them, the lack of a shared sense of partnership can potentially damage the quality of the relationship between parents of ASD children. This supports previous studies on parents of children with ASD that reported the communication between the couple to be a key factor in maintaining a marriage (Gupta et al 2023). Likewise, dyadic coping of parents of children with disabilities, which includes facing the challenges as a team, can have an important role in preserving the marital relationship (Brien-Bérard and des Rivières-Pigeon 2023).…”
Section: Discussionsupporting
confidence: 87%